2019
DOI: 10.15171/jnp.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction and kidney disease

Abstract: Context: Mitochondria play a vital role in producing the energy needed for different cellular activities. The role of mitochondria in different diseases and the aging process is gradually being clarified. Different studies have suggested that mitochondrial dysfunction due to mutations in genes that maintain the integrity of mitochondrial DNA (mtDNA), mitophagy, and apoptosis can lead to many neurological and muscular phenotypes as well as diseases in other organ systems including liver, gastrointestinal tract,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 57 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…Chronic inflammation, oxidative stress, and changes in cellular energy metabolism participate in reduced kidney function [11][12][13]. Mitochondrial dysfunction and reduced CoQ 10 concentration contribute to dysfunctional platelet activity in diseases, such as neurological diseases, cardiovascular diseases, diabetes mellitus, sepsis, Alzheimer's disease, Parkinson's disease, and chronic kidney disease [5,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic inflammation, oxidative stress, and changes in cellular energy metabolism participate in reduced kidney function [11][12][13]. Mitochondrial dysfunction and reduced CoQ 10 concentration contribute to dysfunctional platelet activity in diseases, such as neurological diseases, cardiovascular diseases, diabetes mellitus, sepsis, Alzheimer's disease, Parkinson's disease, and chronic kidney disease [5,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…As an antioxidant, CoQ 10 quenches free radicals and directly prevents lipid peroxidation [9]. Different studies have demonstrated that platelet mitochondrial dysfunction has also been used for studying mitochondria-related diseases [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The human kidney comprises multiple cell populations that are involved in the maintenance of body homeostasis through processes such as blood pressure regulation, nutrient reabsorption, acid-base and electrolyte balance, and hormone secretion (4). Mitochondrial dysfunction is recognized as a leading factor in many renal diseases, including both acute and chronic or end stage renal disease (ESRD) (3,5).…”
Section: Mitochondrial Nephropathiesmentioning
confidence: 99%
“…Mitochondrial dysfunction is implicated in many neurological and muscular phenotypes as well as in diseases of other organ systems including the liver, gastrointestinal tract, heart, and kidneys (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…The mitochondrial dysfunction in the kidney decreased the CoQ 10 level and oxidative stress plays critical roles in the pathogenesis of kidney diseases (33,34). The progression of the disease contributes to changes in cellular energy metabolism, dysfunctional kidney mitochondria (9, 10) and reduced antioxidant protection of the organism (5,26,33,34,35,36,37). In patients suffering from CKD stages 2 and 3, the impaired mitochondrial respiration has been reported to be closely associated with increased oxidative stress (1,38).…”
Section: Plasma Coq 10-total In Subgroups Of Ckd Patients With Concommentioning
confidence: 99%